New Approaches to Dendritic Cell-Based Therapeutic Vaccines Against HIV-1 Infection - Espinar-Buitrago, Marisierra; Muñoz-Fernández, Ma Angeles (Frontiers in Immunology, 2022)
Due to the success of combined antiretroviral therapy (cART) in recent years, the pathological outcome of HIV-1 infection has improved substantially, achieving undetectable viral loads in most cases. Nevertheless, the presence of reservoirs of latently infected cells that form viral reservoirs resulting in patients have to maintain treatment for life. In the absence of effective eradication strategies against Human immunodeficiency virus type 1 (HIV-1), research efforts are focused on obtaining a cure. One of these approaches is the creation of therapeutic vaccines. In this sense, the most promising one up to now is based on the establishment of the immunological synapse between dendritic cells (DCs) and T lymphocytes (TL). DCs are the first cells of the immune system to encounter HIV-1 by acting as antigen presenting cell, allowing the interaction between innate and adaptive immune responses mediated by TL. Furthermore, TL are the end effector and their response capacity is essential in the adaptive elimination of cells infected by pathogens. In this review, we summarize the knowledge about the interaction between DCs-LT, as well as the characterization of the specific T-cell response against HIV-1 infection. Thus, the main point of this review is to analyse the mechanisms and compound is involved in this DCs-TL interaction in order to develop a therapeutic vaccine. In addition, it is intended to research with special emphasis the use of nanotechnology in the design and improvement of vaccines based on dendritic cells.